IMPLEMENTASI DAILY ACTIVITY MONITORING SYSTEM (DAMS) PADA CV. JOGJA MEDIA TELEMATIKA - Tri Munfarida; Yuli Astuti (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
Daily Activity Monitoring System (DAMS) is a web-based system that handles the recording of employee activities, project monitoring and monitoring of employee activities. This system of data processing activities of employees into a report that displays information about the activities of employees, who worked on the project progress and the total time required in the project. CV. Jogja Media Telematika as one of the creative industries are engaged in the field of information technology that has not had an automated recording system activity so that employees tend not to fill and recording and doing activities that are still carried out manually. This makes the process of project monitoring and monitoring employee activity takes a long time and yet ensuring the accuracy of the data, so it requires an automated system for managing employee activity recording, process monitoring projects and activities of employees called Daily Activity Monitoring System (DAMS).From this method the expected results may help the process of automation of recording the activities of employees, project monitoring process and monitoring the activities of employees.